Early identification of potential brain death organ donors based on prediction of spontaneous respiratory arrest - Xu, Guixing; Yang, Yanxia; Wu, Luke; Zheng, Donghua (International Journal of Research in Medical Sciences, 2020)
Background: This study was designed to build a Nomogarm prediction model of spontaneous respiratory arrest (SRA) in nerocritical patients within 72 hours after brain injury for early identification of potential brain death organ donors. Methods: From October 2017 to May 2019, the neurocritical patients admitted to the First Affiliated Hospital of Sun Yat-sen University, were enrolled. The occurrence of SRA within 72 hours after brain injury was regarded as the time interest point and grouping factor, factors associated with SRA were screened by univariate and multivariate analysis, and then the Nomogarm prediction model was developed. Finally, the Nomogarm prediction model was tested in the validation set. Results: In training set, univariate and multivariate analysis showed that the midline shift (OR=4.56, 95% 1.87-19.21), absent of ambient cistern (OR=4.83, 95% 1.35-16.34), cough reflex absence (OR=3.82, 95% 1.15-12.42), intraventricular hemorrhage (OR=3.16, 95% 1.53-14.52) and serum Na+<125mmol/L (OR=3.06, 95% 1.53-13.44) were associated with SRA within 72 hours. In the training set and validation set, the predicted C index of SRA rate within 72 hours was 0.81 (95% CI 0.76-0.85) and 0.80 (95% CI 0.75-0.83), respectively. Further statistical analysis showed that 140 points, 160 points and 170 points were dangerous cut-off points, of which 140 points, 160 points and 170 points were 30.1%, 65.6% and 93.4% associated with SRA within 72 hours, respectively. Conclusions: Nomogram prediction model based on brain injury assessment parameters can predict the time of SRA in neurocritical patients, and can be used for early identification of potential brain death organ donors.